About the teaching of thinking historically and the construction of citizenship, in the analysis of the teaching practice reports of UNC students - Toibero, Desiree (Universidad Nacional del Litoral, 2020)
In this article, from an interpretive methodology, it is proposed to give continuity to a previous work that sought to understand the meanings assigned to citizenship in the curriculum prescribed by the province of Córdoba for the teaching of history in the EGB and its link with the meanings assigned to the teaching of history by students in training from the Universidad Nacional de Córdoba. In particular, it was sought to notice the relationship between the senses attributed to the purpose of forming in thinking historically and the construction of historical consciousness. Starting from these premises, it was investigated the teaching proposals brought to the classrooms by the residents to deepen the understanding of the link between the meanings assigned to the purposes of the teaching of history and their concretion in teaching proposals.